PENGARUH BRAND IMAGE, SOCIAL MEDIA PROMOTION DAN PRICE DISCOUNT TERHADAP LOYALITY MELALUI PURCHASE DECISION PADA UMKM PISANGKEMBUNGLUMER46 SEBAGAI VARIABEL INTERVENING - Lailatul Fitri; Triska Dewi Pramitasari; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
The growth of MSMEs in the culinary sector encourages the need for an integrated marketing strategy to attract and retain customers. In the ever-growing digital era, business actors are required to be able to manage brand image, utilize social media, and offer the right pricing strategy to build customer loyalty. An effective marketing strategy through social media and providing discounts are important factors in attracting consumer attention and increasing loyalty. This study uses a quantitative approach with a survey method by distributing questionnaires to 86 respondents who are consumers of Pisangkembunglumer46. The sampling technique uses simple random sampling, and data analysis is carried out using Smart PLS 3.0 software. The results of the study indicate that Brand Image, Social Media Promotion, and Price Discounts have a significant effect on Purchasing Decisions, and Purchasing Decisions have a significant effect on Customer Loyalty. In addition, it was found that Purchasing Decisions could mediate the influence of Brand Image and Social Media Promotion on Loyalty. However, it did not significantly mediate the influence of Price Discounts. This finding provides important significance for MSMEs in designing digital marketing strategies to increase customer loyalty.